RETRACTED: Cost-effectiveness of development strategy implementation: Key metrics and analysis methods for successful enterprise management - Fedorova Natalya; Glinscaya Anna; Panfilov Ilia; Voronina Elena; Markovskaia Ella (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001